A qualitative study of lay beliefs about influenza immunisation in older people. - Evans, MR; Prout, H; Prior, L; Tapper-Jones, L; Butler, C (2007)
BACKGROUND: Although influenza immunisation is now recommended for all people aged 65 years and over in the UK, many people in that age group still remain unimmunised. AIM: To investigate lay beliefs about influenza and influenza vaccine in older people to identify appropriate ways of promoting vaccine uptake. DESIGN: Qualitative study using narrative interviews. SETTING: Urban and rural communities in South Wales. METHOD: Participants were 54 people aged 65 years and over who were interviewed in their own home. Of these, 11 were regularly immunised, 18 had consistently refused immunisation (refusers), 15 had defaulted (defaulters), five had never been offered immunisation, and five had recently been immunised for the first time. RESULTS: There was an overwhelming consensus among immunised and unimmunised individuals that they were not at risk from influenza. Even if they did catch influenza, they would not suffer from any serious consequences. Refusers and defaulters were more likely to believe that the influenza vaccine had serious side-effects, while the regularly immunised group were more likely to perceive the vaccine as effective. Multiple prompts from family, friends, or primary care staff were important triggers for receiving immunisation. CONCLUSION: Many older people did not feel vulnerable to influenza, regardless of their age, and this influenced their views on the need for immunisation. Both refusers and defaulters overstated adverse effects from influenza vaccine so this is a potential target for an intervention. Individual prompts, particularly from GPs, seemed to be the most significant motivators to attend for immunisation.